Factors Associated with Treatment Delay among Pulmonary Tuberculosis Patients in Public and Private Health Facilities in Addis Ababa, Ethiopia - Adenager, G.; Alemseged, F.; Asefa, H.; Gebremedhin, Amanuel Tesfay (2017)
Background. Early detection and diagnosis of tuberculosis (TB) and the timely commencement of antituberculosis (anti-TB) treatment are the parts of efficient tuberculosis prevention and control program. Delay in the commencement of anti-TB treatment worsens the prognosis and increases the risk of death and the chance of transmission in the community and among health care workers. Objective. To assess tuberculosis treatment delay and associated factors among pulmonary TB patients in Addis Ababa, Ethiopia. Methods. A cross-sectional study was conducted in 10 public and 10 private health facilities that provide TB treatment. The data were collected from 425 newly registered pulmonary TB patients using pretested structured questionnaire from April to June 2012. Data were entered in EPI info version 3.5.1 and analyzed using SPSS version 16.0. Findings. The median durations of a patient, health care system, and total treatment delays were 17, 9, and 35 days, respectively. Overall 179 (42.1%), 233 (54.8%), and 262 (61.6%) of patients experienced patient delay, health care system delay, and total treatment delay, respectively. Distance more than 2.5?km from TB treatment health facility [AOR = 1.6, 95% CI (1.1-2.5)] and the presence of TB-associated stigma [AOR = 2.1, 95% CI (1.3, 3.4)] indicate higher odds of patient delay, whereas, being unemployed, patients with the hemoptysis symptom complain indicated lower odds of health care system delay [AOR = 0.41, 95% CI (0.24, 0.70)] and [AOR = 0.61 (0.39, 0.94)], respectively. Conclusions. A significant proportion of clients experienced patient and health care system delay. Thus, there is a need for designing and implementing appropriate strategies to decrease the delays. Efforts to reduce delays should give focus on integrating prevention programs such as active case detection and expanding access to TB care.